Estudio comparativo de la actividad antibacteriana in vitro de amoxicilina tabletas dispensados en hospitales de la ciudad de Trujillo - Altamirano Sarmiento, Dan Orlando (2009)
In the present work of investigation I compare the activity antibacterial in vitro of Amoxicilina tablets, in cultures of Staphylococcus aureus and Staphylococcus epidermidis betalactamasas negative, by means of the method of double diffusion of Kirby and Bauer. Dilutions of Amoxicilina were used for such purpose tablets given in the hospitals of the city of Trujillo and given commercial Amoxicilina in the pharmacies of the center of Trujillo to the concentration of 25g/10L. The test I am made in 20 cultures for each microorganism obtaining itself like results the following ones: more of 80% of the stocks of Staphylococcus aureus they turned out to be resistant to Amoxicilina given in the hospitals of the city of Trujillo and single 10% I turn out to be sensible, stops Staphylococcus epidermidis but from 85% of the given stocks they turned out to be resistant to Amoxicilina in the hospitals of the city of Trujillo and single 10% turned out to be sensible to the Amoxicilina of the Educational Regional Hospital of Trujillo